The geography of diet variation in Neotropical Carnivora - Cruz, Lívia R.; Muylaert, Renata L.; Galetti, Mauro [UNESP]; Pires, Mathias M. (Wiley, 2022)
Mammalian carnivores (order Carnivora) perform important regulatory functions in terrestrial food webs. Building a comprehensive knowledge of the dietary patterns of carnivorans and the factors determining such patterns is essential for improving our understanding of the role of carnivorans in ecosystem functioning. In the Neotropics, there are 64 extant species of terrestrial Carnivora, but information on their trophic ecology is diffuse. We compiled and analysed the available quantitative dietary data for Neotropical carnivorans, aiming to detect patterns of intraspecific and interspecific dietary variation at a large geographical scale. The resulting database encompasses information on trophic interactions of 37 native carnivoran species from six families across 14 countries. There are clear geographical biases towards southern Brazil, Chile, and Argentina, and a noticeable knowledge gap within the Amazon. Also, most studies are focused on canids and felids, especially Puma concolor, Panthera onca, Cerdocyon thous, Leopardus pardalis, and Chrysocyon brachyurus, whereas for 27 native species, we found no quantitative dietary information. Neotropical carnivorans consume species from at least 651 genera of vertebrates, invertebrates, and plants. We found clear species-specific dietary patterns and marked differences between Neotropical felids and canids. Although predators generally exhibit high levels of consistency in their diets regarding prey body mass, we detected significant intraspecific variation for all species analysed across study sites. Body mass imposes strong constraints on prey use, but biogeographical differences in prey availability and human influence may drive the geographical variation we found. Overall, observed patterns show not only similarities with resource-use patterns found for carnivorans in other continents, such as nestedness driven by body mass, but also differences, such as high levels of frugivory and consumption of invertebrates by canids. Assessing resource-use patterns is the first step towards a better understanding of processes underlying the organisation of trophic interactions, and is imperative for addressing impacts of defaunation on ecosystems and for informing conservation efforts.
Keywords: body mass; Carnivora; diet patterns; Neotropics; spatial variation; synthesis; trophic ecology